Educational outcomes of children with major congenital anomalies: Study protocol for a population-based cohort study using linked hospital and education data from England [version 1; peer review: 2 approved, 1 approved with reservations] - Ruth Gilbert; Ania Zylbersztejn; Bianca De Stavola; Ayana Cant; Laura Gimeno; Katie Harron; Kate Lewis; Joachim Tan; Pia Hardelid; Vincent Nguyen (NIHR Open Research)
Background Major congenital anomalies (CAs) affect around 2% of live births and are a primary cause of infant mortality, childhood morbidity and long-term disability, often requiring hospitalisation and/or surgery. Children with CAs are at greater risk of lower educational attainment compared with their peers, which could be due to learning disabilities, higher rates of ill-health and school absences, or lack of adequate educational support. Our study will compare the educational attainment of children with CAs to those of their peers up to age 11 in England, using linked administrative health and education data. Methods We will analyse data from the ECHILD (Education and Child Health Insights from Linked Data) database. Children born in NHS-funded hospitals from 1st September 2003 to 31st August 2008 whose hospital records were linked to their educational records at three Key Stages (ages 4/5, 6/7 and 10/11 years) will be included. Children with different CAs, indicated by recorded hospital diagnosis codes, will be compared to children without CAs. We will compare the proportions of enrolled children who take the assessment, the proportions who reached national expected levels of attainment, and the mean standardised attainment scores for Maths and English at each Key Stage. We will describe variations in outcome by sex, ethnic minority background, region, and neighbourhood deprivation, and perform regression modelling to compare the attainment trajectories of children with and without CAs, controlling for sociodemographic factors. Ethics and dissemination Ethics approval has been obtained for the analyses of the ECHILD database. Our findings will provide information for parents regarding their children’s expected academic potential, and also enable the development of interventions to support those at risk of not doing well. We will disseminate our findings to academics, policy makers, service users and providers through seminars, peer-reviewed publications, conference abstracts and other media (lay summaries and infographics).